Animals and their products utilized as medicines by the inhabitants surrounding the Ranthambhore National Park, India - Jaroli DP; Mahawar Madan (Journal of Ethnobiology and Ethnomedicine, 2006)
Abstract The present ethnozoological study describes the traditional knowledge related to the use of different animals and animal-derived products as medicines by the inhabitants of villages surrounding the Ranthambhore National Park of India (Bawaria, Mogya, Meena), which is well known for its very rich biodiversity. The field survey was conducted from May to July 2005 by performing interviews through structured questionnaires with 24 informants (16 men and 8 women), who provided information regarding therapeutic uses of animals. A total of 15 animals and animal products were recorded and they are used for different ethnomedical purposes, including tuberculosis, asthma, paralysis, jaundice, earache, constipation, weakness, snake poisoning. The zootherapeutic knowledge was mostly based on domestic animals, but some protected species like the collared dove (Streptopelia sp.), hard shelled turtle (Kachuga tentoria), sambhar (Cervus unicolor) were also mentioned as important medicinal resources. We would suggest that this kind of neglected traditional knowledge should be included into the strategies of conservation and management of faunistic resources in the investigated area.